Magnesium Level and Related Factors in Type 2 Diabetes Mellitus: A Cross-Sectional Study - Konur, Kamil; Polat, Hatice Beyazal; Karavar, Erol; Ayaz, Teslime (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2026)
IntroductionType 2 diabetes mellitus is a chronic metabolic disorder often accompanied by alterations in serum magnesium levels. This study aimed to investigate the relationship between serum magnesium concentration and glycemic control, comorbidities, and medication use in patients with type 2 diabetes mellitus.MethodsA retrospective cross-sectional analysis was conducted using data from 502 patients. Glycemic control was assessed based on HbA1c levels, and serum magnesium concentrations were evaluated concerning clinical and demographic variables. Statistical analyses included t-tests, Mann-Whitney U tests, logistic regression, and ROC curve analysis.ResultsPatients with poor glycemic control had significantly lower serum magnesium levels. Magnesium levels were lower in females, particularly postmenopausal women. Magnesium levels were significantly associated with hypertension, gender, and the use of specific medications such as metformin and indapamide. Logistic regression revealed a significant inverse association between serum Magnesium levels and congestive heart failure (OR = 0.055), but not with other comorbidities. ROC analysis revealed limited predictive value of magnesium for glycemic control (AUC = 0.41).DiscussionAlthough group-level differences in magnesium were evident, magnesium levels alone were not reliable predictors of glycemic control. However, the associations with CHF, HT, gender, and specific medications suggest that magnesium plays a multifaceted role in type 2 diabetes mellitus management.ConclusionRegular monitoring of serum magnesium may aid in identifying at-risk patients, especially those with hypertension, CHF, or on magnesium-depleting medications. Further prospective studies are needed to clarify the clinical utility of magnesium in diabetes care.
Keywords: Magnesium deficiency